Meaning of the experience of tattooing the body on young adults belonging to single-parent families - Barbosa-González, Alejandro (2019)
Background: The purpose of the study was to analyze the meanings attributed by a group of young adults to the experience of recording inscriptions in their bodies. Method: The qualitative method with narrative design was implemented. The technique to collect the information is a free interview. He selected four participants (two women and two men) through a sample intentional. The interviews were recorded on audio and transcribed literally for later analysis. An inductive categorization was carried out. The analysis implemented allowed identifying individual factors and also establishing similarities and differences among participants. Results: The findings show that: This group of young people perform the corporal inscriptions taking as reference significant life and family experiences. Conclusion: It is concluded that the tattoo is a narrative expression that determines ownership over the body and the possibility of being understood and socially validated. The choice of the body part, design and extension; they depend on the importance of what they want to represent.